Variations in Plant Water Use Efficiency Response to Manipulated Precipitation in a Temperate Grassland - Hai, Xuying; Li, Jianping; Li, Jiwei; Liu, Yulin; Dong, Lingbo; Wang, Xiaozhen; Lv, Wenwen; Hu, Zhenhong; Shangguan, Zhouping; Deng, Lei (Frontiers in Plant Science, 2022)
Analyzing the variability in water use efficiency (WUE) in response to manipulated precipitation can improve our understanding of the interaction between carbon and water cycles in the plant-soil-atmosphere system. However, little is known regarding the impact of altered precipitation on plant WUE in arid and semi-arid regions. The study examined the effects of altered precipitation (i.e., ambient precipitation (100% of natural precipitation), decreased precipitation (DP, -50%), and increased precipitation (IP, +50%)) on the WUE of two functional groups which included grass species (Stipa grandis and Stipa bungeana) and forb species (Artemisia gmelinii), and explored the controlling factors in a temperate grassland of the Loess Plateau, China. We found that WUE was significantly affected by growth stages, precipitation treatments, and their interactions (p < 0.001). DP increased the WUE of S. grandis and S. bungeana generally, however, IP decreased WUE especially in A. gmelinii. In addition, the WUE was higher in grasses than forbs, and which in the initial growth stage was lower than that in the other growth stages. Soil temperature, soil available nutrients (i.e., NO3--N, NH4+-N, AP) and soil microbial activity were the main factors affecting WUE of plants. Altered precipitation directly changed soil moisture and temperature, influencing soil nutrient status and microbial activity thereby affecting plant WUE in the grasslands. These findings highlighted that the grass species with high resource competitiveness and WUE can be selected for vegetation restoration in arid and semi-arid areas.